2017
DOI: 10.1080/14017431.2017.1343493
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of local carotid stiffness in seronegative and seropositive rheumatoid arthritis

Abstract: RA per se is sufficient to cause arteriosclerosis in the absence of classical CV risk factors. However, arterial hypertrophy is only increased in seronegative patients but not in seropositive group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…As seen in this study, age, SBP, and BMI have been previously identified as independent predictors of arterial stiffness in RA patients 21,23,24,39 . However, the effect of age on PWV, mediated by SBP and BMI, has not been previously described.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…As seen in this study, age, SBP, and BMI have been previously identified as independent predictors of arterial stiffness in RA patients 21,23,24,39 . However, the effect of age on PWV, mediated by SBP and BMI, has not been previously described.…”
Section: Discussionsupporting
confidence: 66%
“…Some case-control studies reported increased arterial stiffness in RA patients 11–13 . In these studies, associations with variables that are characteristic of the disease such as disease duration 14,15 , inflammatory variables 1619 , and disease activity 16,20–22 have been demonstrated, although arterial stiffness has also been correlated with age 19,23,24 and SBP 2325 . There are few published studies that have evaluated distensibility as a marker of arterial stiffness in RA 26 , and the results of these studies are similar to those obtained for PWV and AIx.…”
Section: Introductionmentioning
confidence: 99%
“…The sample size calculation was based on studies in which the PWV values and differences (to assess vascular stiffness) between patients with RA and controls without RA were estimated ( 14 , 15 , 17 ). A power of 80% and a type I error of 0.05 were assumed.…”
Section: Methodsmentioning
confidence: 99%
“…In fact, there are studies evaluating the PWV in RA but not many that assess VA, and few or none that analyze VA based on PWV in RA patients (14)(15)(16)(17)(18)(19). For instance, Mong et al used the coronary calcium score (CCS) as a non-invasive method to calculate arterial age and cardiovascular risk stratification.…”
Section: Introductionmentioning
confidence: 99%
“…Although it can affect anyone at any age, the peak onset is between the ages of 50 and 59 [2]. RA patients have an increased risk of cardiovascular (CV) disease occurring due to the inflammatory nature of the disease leading to higher morbidity and mortality rates [3][4][5]. CV events associated with RA range in a spectrum of severity.…”
Section: Introductionmentioning
confidence: 99%